Design of Performance Indicators in Warehouse Management - Anindita Rahmalia Putri; Bayu Wahyudi; Anindita Rahmalia Putri (Universitas Mercu Buana, 2023)
To maintain the continuity of product flow in the supply chain system, good warehouse management is needed. Dynamic market conditions are able to cause instability in the product flow. Moreover, there are many disruptions occur as technology continues to develop in Indonesia. This instability will indirectly affect the warehouse performance in a company. So, to minimize the effects of instability, it is necessary to design indicators that are used as a reference for designing mitigation strategies and as a controlling tool so that the company's growth is relevant to the objectives that have been created. In addition, these indicators can be used as a benchmark to improve the warehouse regularly. So, this research aims to design performance indicators in warehouse management that can be used as a measurement reference to increase warehouse productivity. The result showed that there are 17 validated indicators which are categorized into 5 dimensions. These dimensions are 4 cost dimension indicators, 4 productivity dimension indicators, 3 quality dimension indicators, 4 time dimension indicators, and 2 utilization dimension indicators.